Grau de concordância da classificação de risco de usuários atendidos em um pronto-socorro utilizando dois diferentes protocolos - Cristiane Chaves de Souza (2009)
Brazilians live daily with an overcrowding in the emergency room that is exacerbated by organizational problems such as care by order of arrival, no establishment of clinical criteria. The implementation of risk classification has been a measure taken by the Ministry of Health to organize the demand and humanization of care, in order to minimize the risk to patients waiting for medical attention. The nurse has been appointed as the professional most qualified to perform the risk assessment, and legally protected by a protocol to support the decision. The objective of this study was to assess the degree of agreement between an institutional protocol and the protocol of Manchester to the risk assessment of patients attended seen in the emergency room of a public hospital in Belo Horizonte - MG. This is a descriptive-comparative study, where 382 reports of patients in the emergency room were evaluated and the risk was classified using two protocols: the protocol established in the institution and the protocol of Manchester. To determine the degree of agreement between the protocols indices were calculated by weighted and unweighted kappa. Statistical tests were used to identify the factors that influenced the agreement and disagreement between the protocols. The results showed that the correlation between the protocols is average, when considering the classification errors occurred between neighboring colors (kappa = 0.48), and good when considering the classification errors occurred between extreme colors (kappa = 0.61). The protocol of Manchester increased the level of priority of patients when compared to the institutional protocol. The Manchester protocol has been proven to be more inclusive. The findings of ineffective breathing, severe pain, fever, pain and a no recent problem are decisive complaints for the classification of patients in both protocols in the colors red, orange, yellow, green and blue. The age and complete record of the complaint are the main factors influencing the outcome of the risk rating to the protocol established in the institution.